3D Printing Technology in Drug Delivery: Recent Progress and Application - Kotta, Sabna; Nair, Anroop; Alsabeelah, Nimer (Current Pharmaceutical Design, 2018)
Background: 3D printing technology is a new chapter in pharmaceutical manufacturing and has gained vast interest in the recent past as it offers significant advantages over traditional pharmaceutical processes. Advances in technologies can lead to the design of suitable 3D printing device capable of producing formulations with intended drug release. Methods: This review summarizes the applications of 3D printing technology in various drug delivery systems. The applications are well arranged in different sections like uses in personalized drug dosing, complex drugrelease profiles, personalized topical treatment devices, novel dosage forms and drug delivery devices and 3D printed polypills. Results: This niche technology seems to be a transformative tool with more flexibility in pharmaceutical manufacturing. Typically, 3D printing is a layer-by-layer process having the ability to fabricate 3D formulations by depositing the product components by digital control. This additive manufacturing process can provide tailored and individualized dosing for treatment of patients different backgrounds with varied customs and metabolism pattern. In addition, this printing technology has the capacity for dispensing low volumes with accuracy along with accurate spatial control for customized drug delivery. After the FDA approval of first 3D printed tablet Spritam, the 3D printing technology is extensively explored in the arena of drug delivery. Conclusion: There is enormous scope for this promising technology in designing various delivery systems and provides customized patient-compatible formulations with polypills. The future of this technology will rely on its prospective to provide 3D printing systems capable of manufacturing personalized doses. In nutshell, the 3D approach is likely to revolutionize drug delivery systems to a new level, though need time to evolve.
Keywords: 3D printed polypill